Boosting Titanium Surfaces with Positive Charges: Newly Developed Cationic Coating Combines Anticorrosive and Bactericidal Properties for Implant Application - Silva, João Pedro dos S.; Costa, Raphael C.; Nagay, Bruna E.; Borges, Maria H. R.; Sacramento, Catharina M.; da Cruz, Nilson C. [UNESP]; Rangel, Elidiane C. [UNESP]; Fortulan, Carlos A.; da Silva, José H. D. [UNESP]; Ruiz, Karina G. S.; Barão, Valentim A. R. (American Chemical Society (ACS), 2023)
Along with poor implant-bone integration, peri-implant diseases are the major causes of implant failure. Although such diseases are primarily triggered by biofilm accumulation, a complex inflammatory process in response to corrosive-related metallic ions/debris has also been recognized as a risk factor. In this regard, by boosting the titanium (Ti) surface with silane-based positive charges, cationic coatings have gained increasing attention due to their ability to kill pathogens and may be favorable for corrosion resistance. Nevertheless, the development of a cationic coating that combines such properties in addition to having a favorable topography for implant osseointegration is lacking. Because introducing hydroxyl (−OH) groups to Ti is essential to increase chemical bonds with silane, Ti pretreatment is of utmost importance to achieve such polarization. In this study, plasma electrolytic oxidation (PEO) was investigated as a new route to pretreat Ti with OH groups while providing favorable properties for implant application compared with traditional hydrothermal treatment (HT). To produce bactericidal and corrosion-resistant cationic coatings, after pretreatment with PEO or HT (Step 1), surface silanization was subsequently performed via immersion-based functionalization with 3-aminopropyltriethoxysilane (APTES) (Step 2). In the end, five groups were assessed: untreated Ti (Ti), HT, PEO, HT+APTES, and PEO+APTES. PEO created a porous surface with increased roughness and better mechanical and tribological properties compared with HT and Ti. The introduction of −OH groups by HT and PEO was confirmed by Fourier transform infrared spectroscopy and the increase in wettability producing superhydrophilic surfaces. After silanization, the surfaces were polarized to hydrophobic ones, and an increase in the amine functional group was observed by X-ray photoelectron spectroscopy, demonstrating a considerable amount of positive ions. Such protonation may explain the enhanced corrosion resistance and dead bacteria (Streptococcus aureus and Escherichia coli) found for PEO+APTES. All groups presented noncytotoxic properties with similar blood plasma protein adsorption capacity vs the Ti control. Our findings provide new insights into developing next-generation cationic coatings by suggesting that a tailorable porous and oxide coating produced by PEO has promise in designing enhanced cationic surfaces targeting biomedical and dental implant applications.
Keywords: antimicrobials; corrosion; dental implants; surface treatment; titanium